The Effect of Extra Curricular Programs and Parental Involvement on the Discipline of Middle School Students in Bogor District, West Java - Nur Rizkiyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Discipline is something students must have in the current digital age. Discipline is an absolute requirement in fulfilling learning in schools. The active role of parents becomes important when there are assignments from the teacher or extracurricular activities at school. The purpose of this research is to determine the effect of extracurricular activities on discipline, and to determine the effect of parental involvement on discipline and extracurricular directing and parental involvement on discipline. This research uses quantitative methods. The results showed that there was an effect of extracurricular activities on discipline, and there was an effect of parental involvement on discipline simultaneously